Exploring the Occurrence of Clogging in Highly Permeable Coarse Soils of Dam Foundations - Jianquan Ma; Hao Peng; Shibo Li; Zhao Duan; Xinshe Zhang; Donghe Ma (Advances in Civil Engineering)
Leakage through the permeable coarse soils of dam foundations in Tibet, China, lessened over time without any additional antiseepage measures. In fact, clogging generated during the infiltration process is recognized as the major factor in reducing leakage. A laboratory study was conducted to understand clogging in highly permeable coarse soil of a dam foundation with the primary aim of determining the clogging patterns and optimum clogging particle size (PS). Seven replicate experiments were constructed using soil media with PS ranges of 32–64 mm, 16–32 mm, 8–16 mm, 4–8 mm, 2–4 mm, 1-2 mm, and 0.5–1 mm to observe clogging after feeding the soil media with sediments of different PSs. The experimental results showed that four clogging patterns were formed in different PSs of the coarse foundation soil. The ratio of the effective aperture of the soil Dea and the equivalent clogging particle size dede/Dea had a dominant effect on the four clogging patterns (surface clogging, de/Dea>1; surface-internal clogging, 0.5<de/Dea≤1; internal partial pore blockage, 0.25<de/Dea≤0.5; and unclogging, de/Dea≤0.25). The assessment criterion of the optimum clogging pattern was determined by 0.5<de/Dea≤1, and from that, the optimum clogging PS do was calculated.